SUPPLY CHAIN PERFORMANCE WITHIN AGRI FOOD SECTOR - Daniela Dinu, Magdalena (Economics of Agriculture, 2016)
By setting the goals of this scientifc paper has been outlined the research methodology. Thus were developed conclusion, and by using the methods, procedures, techniques, rules and tools and know-how has been demonstrated the central hypothesis: "Inside the agri-food supply chain is created value through operations and logistics activities." The value created leads to competitive advantages in order to identify companies within market, gaining loyal consumers. The article presents the components of agri-food supply chain, the main Key Performance Indicators measuring its performance, the difference between a traditional supply chain and sustainable supply chain by analyzing the waste management component. In order to get professional expertise referring to Key Performance Indicators a quantitative research has been organized. In closing the article present the development strategies of agri-food supply chain.